MORPHOLOGICAL CHARACTERISTICS OF 12 WATERMELON (Citrullus lanatus) PURE LINES AT THE F5 GENERATION - Wahyudi, Anung; Sari, Miranda Ferwita; Hendrianto, Yohanes (Jurnal Agrotek Tropika, 2024)
Indonesia faces a shortfall in watermelon seed production, with domestic output reaching only 12.50 tons compared to a national demand of 14.70 tons. This shortage leads to high seed prices, limiting access for local farmers and negatively affecting production sustainability. Developing high-yielding, superior watermelon varieties is a strategic solution to strengthen national seed independence. This study aimed to evaluate the morphological diversity of 12 pure watermelon lines at the F5 generation, which will serve as potential parental genotypes for further breeding efforts. The research employed a Randomized Block Design (RCBD) with a single factor genotype and included observations on both qualitative and quantitative traits. Notable genotypes with unique rind coloration were WM 03-27-2, WM 08-6-3, and WM 12-1-5. Among them, WM 03-27-2 exhibited superior performance in key quantitative traits, including fruit weight, length, diameter, rind thickness, seed count, seed weight per fruit, and 100-seed weight. Although all genotypes produced seeds in the low-yield category, each displayed unique traits of potential value in breeding programs. Cluster analysis based on qualitative characteristics grouped the genotypes into two main clusters at a 75% similarity level, with Cluster I containing 11 genotypes and Cluster II consisting solely of WM 03-27-2. This research contributes to addressing the critical need for locally adapted, high-performing watermelon varieties in Indonesia and provides foundational data for future breeding strategies aimed at achieving seed self-sufficiency.